The Ịjọ Praise-Poet: Chief Adolphus Munamuna in Performance - Armstrong, Imomotimi (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
There is no dearth of studies on how the African praise-poet renders his poems in performance in African oral literature scholarship. However, Africanist scholars in the disciplines of performance studies, folklore, anthropology and literary studies have not extended such studies to the Ịjọ praise-singer, Chief Adolphus Munamuna. Therefore, this study examines the manner in which the Ịjọ bard performs his chants. First, it begins with a survey of the historical development of the performance approach to the study of folklore and, thereafter, compares the way Chief Munamuna performs his chants to other praise-singers on the African continent. The paper notes that the Ịjọ verbal artist performs the same way others perform. It further points out that the utilization of a cell phone to audio-record praises or poems by Chief Munamuna himself during a performance is what, perhaps, marks him out among his colleagues elsewhere in Africa. Data for the study was gathered from observations of live performances of the praise-poet. The study will appeal to folklore and oral literature scholars because it has contributed to existing scholarship on the nexus between performance and the African bard. More importantly, it has generated awareness about the use of a cell phone by a bard to record his own live performances in order to preserve them for posterity.